2012
DOI: 10.1111/j.1365-294x.2012.05740.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of source‐sink dynamics in mountain lions of the Great Basin

Abstract: Natural and anthropogenic boundaries have been shown to affect population dynamics and population structure for many species with movement patterns at the landscape level. Understanding population boundaries and movement rates in the field for species that are cryptic and occur at low densities is often extremely difficult and logistically prohibitive; however genetic techniques may offer insights that have previously been unattainable. We analysed thirteen microsatellite loci for 739 mountain lions (Puma conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 64 publications
(179 reference statements)
5
88
0
Order By: Relevance
“…For example, using genetic methods, (Andreasen et al 2012) observed asymmetrical movement of mountain lions (Puma concolor) among local populations consistent with expectations of a source-sink population structure. Similarly, (Dharmarajan et al 2014) utilized a novel approach for quantifying fine-scale genetic attributes (i.e., parentage and kin structure) of local populations of raccoons (Procyon lotor) within a fragmented agricultural landscape to determine how demographic and behavioral factors contribute to variance in kin-structure amongst local populav www.esajournals.org tions.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…For example, using genetic methods, (Andreasen et al 2012) observed asymmetrical movement of mountain lions (Puma concolor) among local populations consistent with expectations of a source-sink population structure. Similarly, (Dharmarajan et al 2014) utilized a novel approach for quantifying fine-scale genetic attributes (i.e., parentage and kin structure) of local populations of raccoons (Procyon lotor) within a fragmented agricultural landscape to determine how demographic and behavioral factors contribute to variance in kin-structure amongst local populav www.esajournals.org tions.…”
Section: Introductionsupporting
confidence: 61%
“…The use of molecular techniques to elucidate spatial heterogeneity in population dynamics represents a substantial advancement in our ability to distinguish potential source and sink populations, particularly for large and secretive mammals (Peery et al 2008, Andreasen et al 2012, Dharmarajan et al 2014. For example, using genetic methods, (Andreasen et al 2012) observed asymmetrical movement of mountain lions (Puma concolor) among local populations consistent with expectations of a source-sink population structure.…”
Section: Introductionmentioning
confidence: 89%
“…This is a recommended approach for populations connected by high ongoing gene flow since the 'F model' accepts deviations from genetic equilibrium (Faubet and Gaggiotto 2008;Andreasen et al 2012. We implemented simulations with the two data sets, each containing one tundra cell (20 9 20 km) with a sample size of n [ 10 individuals (termed Helags and Borgafjall respectively) and all neighboring boreal cells (termed Boreal1-5).…”
Section: Estimating Recent Dispersal Ratesmentioning
confidence: 99%
“…Including genetic analysis as a tool can thus supplement management decisions with information about the recent and historical origin, composition and connectivity of expanding populations (Estoup and Guillemaud 2010). In addition to this, modern analytical approaches allow for recent migration routes and dispersal rates to be disseminated (Andreasen et al 2012). Hence, in order to formulate realistic management approaches and to predict the future impact of invasions, it is necessary to retrieve detailed information about the fine-scaled expansion patterns and dispersal routes of highly influential and expanding species (Rollins et al 2009;Estoup and Guillemaud 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals in a population are often forced to move due to natural dispersal events (Ruth et al 2011) or dispersal driven by high densities above carrying capacity (Benson and Chamberlain 2007). When an animal leaves an area (a source) it may disperse into a sink, which is a habitat of lower quality or of apparent high quality, but nonetheless associated with low survival rates (Andreasen et al 2012;Ruth et al 2011). Differences between source and sink habitats are especially evident in areas where mortality risk occurs in pulses, such as hunting seasons, allowing influx of individuals during the off-season.…”
Section: Introductionmentioning
confidence: 99%